ROLE OF INNOVATION MANAGEMENT IN ENSURING ECONOMIC STABILITY (Marketing Journal, 2025)
At the modern stage of economic development , the high volatility and complexity of economic systems necessitate the deep integration of innovative approaches into management practices . This study provides a comprehensive analysis of the systemic and institutional role of innovation management in ensuring economic stability . Particular attention is given to the strategic planning functions of innovation management , digital transformation , mobilization of scientific and technical potential , and enhancing the adaptive competitiveness of economic entities . 92
Keywords: Innovation management; economic sustainability; digital transformation; innovation strategy; competitiveness; knowledge -based economy; technological development; adaptive management